APPLICATION OF WEB-BASED DECISION SUPPORT SYSTEM FOR SUBSIDIZED 3 KG LPG DISTRIBUTION ROUTE OPTIMIZATION USING CLARKE AND WRIGHT SAVINGS ALGORITHM - Melissa Chandra; Lasker Pangarapan Sinaga (Kresnamedia Publisher, 2026)
The distribution of subsidized 3 kg LPG cylinders often relies on manually planned routes based on drivers’ experience, resulting in inefficient distribution operations. This study aims to develop a web-based Decision Support System integrated with WebGIS visualization for optimizing subsidized 3 kg LPG distribution routes using the Clarke and Wright Savings Algorithm. The research method consisted of problem analysis, literature review, data collection, route optimization, system development, and system evaluation. Route optimization was performed using demand data from 22 LPG outlets while considering vehicle capacity constraints. The optimization results generated five distribution routes with a total travel distance of 85.87 km, compared with 98.78 km for the company's existing routes, resulting in a distance reduction of 12.91 km (13.06%). System verification showed that the system produced results identical to manual Clarke and Wright Savings calculations. Blackbox Testing indicated that all system functions operated successfully, while User Acceptance Testing (UAT) achieved a score of 91.8%, indicating a very high level of user acceptance. These results demonstrate that the developed system can support more efficient and systematic LPG distribution planning.